Promosi Penjualan, Store Atmosphere, Dan Brand Image Berpengaruh Terhadap Repurchase Intention (Studi Kasus Pada Cafe Ortho Kopi Malang - Sandra Oktaviasari; Rois Arifin; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract The purpose of this study was to determine sales promotion, store atmosphere and brand image effect on repurchase intention at ortho kopi coffee house malang. By using a sample of consumers at ortho kopi coffee house malang, the results show that partially sales promotion, store atmosphere, and brand image has a positive and significant effect on repurchase intention. Simultaneously sales promotion, store atmosphere and brand image together have a positive and significant effect of 83.1% and the remaining 16.9% is influenced by other variables that are not explained in this study. Keywords: brand image, store atmosphere, sales promotion, repurchase intention